2018
DOI: 10.1080/01480545.2018.1497047
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and teratogenicity of seabuckthorn (Hippophae rhamnoides L.) berry oil

Abstract: As botanicals and dietary supplements are used increasingly in many countries, the issue of safety is particularly critical for regulation of food products containing these substances. Seabuckthorn (Hippophae rhamnoides L.) has been used for centuries as a medicine and nutritional supplement in Asia and Europe. However, data regarding to the safety assessment of the plant and its extracts is still rare. This study was to evaluate the potential toxicity of seabuckthorn berry (SB) oil conducted in three genotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Acute and sub-chronic toxicity studies performed in Wistar rats have shown no signs of toxicity and reported a no-observed-adverse-effect level of 10 ml/kg body weight (Zhao et al, 2017). Furthermore, no mutagenicity was observed from the SBKT exposure in histidine-dependent Salmonella typhimurium stain (Wen et al, 2018), suggesting no induction of genotoxicity by SBKT. Exposure to SBKT also did not induce any changes in sperm morphology and micronucleus formation rate in polychromatic erythrocytes obtained from mice orally treated with the oil (Wen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute and sub-chronic toxicity studies performed in Wistar rats have shown no signs of toxicity and reported a no-observed-adverse-effect level of 10 ml/kg body weight (Zhao et al, 2017). Furthermore, no mutagenicity was observed from the SBKT exposure in histidine-dependent Salmonella typhimurium stain (Wen et al, 2018), suggesting no induction of genotoxicity by SBKT. Exposure to SBKT also did not induce any changes in sperm morphology and micronucleus formation rate in polychromatic erythrocytes obtained from mice orally treated with the oil (Wen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, no mutagenicity was observed from the SBKT exposure in histidine-dependent Salmonella typhimurium stain (Wen et al, 2018), suggesting no induction of genotoxicity by SBKT. Exposure to SBKT also did not induce any changes in sperm morphology and micronucleus formation rate in polychromatic erythrocytes obtained from mice orally treated with the oil (Wen et al, 2018). In the present study, we have not seen any change in the animal weights, food, or water consumption (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…However, data regarding to the cytotoxicity and genotoxicity of the seabuckthorn and its extracts are still scarce. Efforts have been spent to explore the pharmacological activities while only a few studies have focused on the safety evaluation of the plant extracts [59,60]. In a study on mice, the maximum tolerated dose of seabuckthorn oil was >20 mL/kg for mice in relation to acute toxicity, and the no-observed-adverse-effect level was of 10 mL/kg body weight in both male and female rats regarding the 90-day toxicity study [61].…”
Section: Discussionmentioning
confidence: 99%
“…In scientific periodicals, there are quite few research articles dedicated to the study of sea buckthorn and its physiological effects, despite the fact that this product has been used in medical practice and nutrition of Asia and Europe for many centuries [23]. However, the nutritional composition of sea buckthorn allows us to recognize this product as bio-functional, which indicates the feasibility of its use in food technology for the products with functional properties [24,25].…”
Section: Discussionmentioning
confidence: 99%